Apoio à exportaç\~ao: Evidências empíricas e desafios para futuras pesquisas - Flávia de Holanda Schmidt; Jorge Ferreira da Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– The strengthening of the commitment to export assistance and the establishment of comprehensive programs to foster export activities of firms are part of public policies in almost all developed and developing countries. In recent decades, not only the amount devoted by governments to these actions increased as the number of trade and investment promotion agencies has tripled worldwide in the context of the development of national export strategies. Despite academic contributions on the topic have been on the agenda of many authors for over thirty years, conceptual and methodological issues have contributed to huge disagreement regarding the real effects and impacts of the adoption of export promotion programs in the export performance of supported firms. Considering that government resources are scarce and require maximum effort to better allocative efficiency and thus, public policies must be strongly based on evidence, a significant amount of empirical studies in International Business devoted to export assistance was recently developed. This paper aims to identify the current state of issues related to export promotion and develop a deeper understanding of the phenomenon, departing from a review of empirical work on the subject published between 1992 and 2011. The year 1992 was set as a reference for the beginning of the period because the work of Diamantopoulos, Schlegelmilch and Tse (1993), the last review on the topic identified, encompassed the period between 1971 and 1991. All of the 25 identified articles were coded according to the same method of analysis, based on objective criteria. The analysis indicates that the production has evolved in quantity and quality between the two time periods in which the whole period was split, and highlights an evolution over the period analyzed, specially in relation to the diversification of the loci of research, the adoption of more robust statistical techniques and the emergence of longitudinal studies. Some limitations, however, were still observed even in more recent studies, and in these cases, some recommendations are made. Once the export promotion is one area in which research in International Business can generate contributions that are both useful for policymakers and practitioners, this work is expected to sum up important issues that can be useful for developing better empirical investigations on the subject in the future.
Keywords: F23; M16; M38; 330; internationalization; export assistance; export performance; Globalisierung; Außenwirtschaftsförderung